PREVALENCE OF MPDS Vs DISC DISORDERS - Reddy, B. Aishwarya; Sasanka, Keerthi; K, Venkatesh.; B, Nivethigaa. (International Journal of Psychosocial Rehabilitation, 2025)
The Temporomandibular joint acts like a sliding hinge, connecting the jawbone to the skull. A temporomandibular disorder can cause pain in the jaw joint and in the muscles that control jaw movement. Some people who have jaw pain also tend to clench or grind the teeth called bruxism.Injury to the jaw, the joint, or the muscles of the head and neck can lead to temporomandibular disorders. Stress, which causes tightening of facial and jaw muscles or clenching of teeth can also be one of the most common reasons for temporomandibular disorders. The aim of this study is to check the prevalence of Myofascial pain dysfunction syndrome and Disc Condyle disorders in patients suffering from Temporomandibular disorders. Data from 86000 patients visiting Saveetha Dental College during the time period of June 2019 to March 2020 were reviewed and the data was collected. The data was taken from the category - temporomandibular disorders. A total of 61 patients were taken and analysed for MPDS and Disc condyle disorders. The results were tabulated and analysed using SPSS software by IBM. Out of 61 patients, 57.4%of them had disc condyle disorder, 34.4% had MPDS, 3.3% of them had Degenerative disorder and 4.9% of the patients did not show any disorder. The prevalence of disc condyle disorder is much higher than myofascial pain dysfunction syndrome.